The process of processing Big data in the model of an intelligent transport system of a Smart city - Zhukabaeva, Т.K.; Akhayeva, Ж.Б.; Zakirova, А.; Merzadinova, Т.; Zhmud, В.А. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2021)
The article discusses the process of applying big data analysis to solve the problems of traffic analysis in the Smart city of Nur-Sultan. There is substantiated relevance of the model of the intellectual system of development of the transport system of the metropolis.There is carried out review of modern approaches in the field of development and intellectualization of transport systems. The formal development of the system is carried out in a logical-algorithmic language. The article describes its external and internal structure. The proposed solution is based on the Flowmap.blue parallel computing model. There are analyzed two experimental cases such as assessment of the quality of public transport based on the analysis of the history of the location of buses, and assessment of passenger mobility by analyzing the history of ticket purchases from transport cards on weekdays and weekends. Both experiments use a real database of the public transport system in the city of Nur-Sultan, Republic of Kazakhstan.